Literature Review: The Chemical Composition and Pharmacological Activities of Nannochloropsis sp - Ulfiyah, Ryhadatul; Hijriadina, Zerati; Oktari, Baiq Khaeratinnisa; Anjanisa, Diah Hikmatin; Magvirahandini, Reivirly Khairadaty; Mutthoimah, Ulfatul; Listyacahyani, Anggit (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The microalga Nannochloropsis sp. is a potential bioactive source with various applications in the pharmaceutical and health industries. This study aims to identify its chemical composition and evaluate its pharmacological activities, including antioxidant, antidiabetic, antibacterial, antihyperlipidemic, and cytotoxic properties. The method involves a literature review of relevant and recent scientific articles using specific keywords. The results indicate that Nannochloropsis sp. is rich in bioactive compounds, such as unsaturated fatty acids, flavonoids, and phenolics, which contribute to its biological activities. This microalga has been shown to effectively inhibit pathogenic bacterial growth, reduce blood sugar, cholesterol, and lipid levels, and possess potential anticancer activity. The study concludes that Nannochloropsis sp. has promising prospects as a natural raw material source for modern drug development. Further research is recommended to explore the mechanisms of its bioactive compounds and to develop formulations for products based on this microalga.